The Description of Mental Health and Emotional Mental Disorders of Students And Families During Covid-19 Pandemic - Sulistyorini, Ariani; Pujianto, Tutut (Universitas STRADA Indonesia, 2020)
Background: The Covid-19 pandemic could have an adverse impact on both physical and psychosocial conditions. Physical distancing encourages a person to be unable to perform activities normally to reduce the likelihood of transmission. Physical distancing must be done by everyone, including students and their families. This condition can lead to feelings of loneliness, boredom, and anxiety. Another impact that society feels is the onset of unrest due to financial condition, employment, and future life plans. Anxiety and anxiety caused by the Covid-19 pandemic resulted in the emergence of mental health problems and emotional mental disorders. Purpose: This study aimed to find out the picture of mental health and emotional mental disorders in students and families during the Covid 19 Pandemic.Methods: The research design used is a descriptive crossectional. The population in this study was students of Nursing Diploma 3 Study Program STIKES Karya Husada Kediri and his family. Fifty-six students were selected as sample members, through random sampling techniques. The variables in this study were mental health and emotional mental disorders. Data retrieval is carried out from 6 to 20 June 2020, with the instrument Self Reporting Questionnaire (SRQ-29). Descriptive analysis of data is performed with the help of frequency distribution tables.Results: The results of the study found that there were 2 respondents (3.6%) psychological disorders (anxiety and depression), none (0%) psychoactive disorders/drug use. Research data also shows that there are 5 respondents (8.9%) psychotic disorders, as well as 16 respondents (28.6%) PTSD disorder. Mental health disorders experienced by respondents are emotional mental disorders with symptoms of fear, worry, anxiety, tension and even excessive headaches. Mental health disorders result in impaired daily life activities.Conclusion: To prevent an increase in the number of people with emotional mental disorders in students and their families, there needs to be educational efforts that contain how to avoid and overcome emotional mental disorders that occur and the need for psychosocial mental health support in students and their families